The Use of Interactive Methods in Teaching the Russian in Technical Universities of Kazakhstan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article aims to consider business simulation games and empirical training abroad as a part of continuing education system with a focus on their practical significance and value for socialization for water management students. Programs of Moscow Timiryazev Agricultural Academy and foreign real and virtual simulation games scenarios were used as materials. The comparative method and the methods of modeling and visualization were applied. The examples of business simulation game implementations in the field of water management, including Aqua Republica, International Drought Tournament, Shariva and Ravilla, were studied and the main advantages of such games were pointed out. The two options of seasonal practice in Europe planned by the Russian State Agrarian University — Moscow Timiryazev Agricultural Academy and the experimental Canadian-Cuban program of training abroad were analyzed in detail as an example of the effective practical learning. After the comparison of Russian and foreign practices the formula of any new method in today’s higher education has been provided and the most effective blended learning methods have been pointed out. The results of the study can be used in the development of curricula and courses of agrarian higher educational establishments in Russia and abroad.